THE LIVED EXPERIENCE OF PATIENTS WITH HEMATOLOGICAL CANCER AFTER TREATMENT: AN INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Dr Zarghuna Naseem; Muhammad Jawad Nasir Malik; Zainab Mazhar (International Journal of Contemporary Issues in Social Sciences, 2024)
The research aimed to investigate the effect of haematological cancer and its treatment on patient’s different aspects of life. The lived experiences were examined using an Interpretative Phenomenological Analysis (IPA). The purposive sampling strategy was used and 6 participants were selected from Pakistan. An open-ended semi-structured interview protocol was developed after a literature review and focus group discussion. It covered topics like diagnosis, treatment, coping mechanisms, support systems, and life post-treatment of the patients. Participants were assigned pseudonyms to maintain their anonymity in the data analysis and reporting. Data were collected through the Social Media app. Voice recordings of the interviews were transcribed, converting spoken words into written text. NVivo 12 software was used for Interpretative Phenomenological Analysis. The textual data were imported into the N Vivo software. Using NVivo 12's coding feature, the researcher initiated identifying and generating initial codes. An inductive approach was followed, enabling the emergence of themes and patterns directly from the participants' accounts. Graphic representation of the data was done through word trees, word clouds and graphics. Five superordinate themes were identified: Reactions towards disease, challenges during disease, social support, coping mechanisms and personal growth after treatment. Several sub-themes emerged from the narratives of the participants which highlighted the emotional, physical and social sufferings they encountered during their journey from the diagnosis to the treatment of cancer. Implications for the clinicians and caregivers were discussed.